High Energy Storage Efficiency Triboelectric Nanogenerators with Unidirectional Switches and Passive Power Management Circuits. (23rd October 2018) - Qin, Huaifang; Cheng, Gang; Zi, Yunlong; Gu, Guangqin; Zhang, Bao; Shang, Wanyu; Yang, Feng; Yang, Junjie; Du, Zuliang; Wang, Zhong Lin
Abstract: The high‐voltage and low‐current output characteristics of a triboelectric nanogenerator (TENG) make itself difficult for directly powering small electronic devices. A power management circuit (PMC) is indispensable to address the impedance mismatch issue. In this paper, a TENG with a unidirectional switch (TENG‐UDS) is developed, which can provide the maximized output energy regardless of the load resistance. A passive PMC with a simple structure and high energy storage efficiency is designed based on this TENG‐UDS, which is made up of all passive electronic components, including an inductor, a diode, and a capacitor. Theoretical calculations show that the theoretical energy storage efficiency of the passive PMC can reach 75.8%. In the actual experiment of charging a capacitor, the measured energy storage efficiency can reach 48.0%. It is demonstrated that the electronic watch and high‐brightness quantum dot light‐emitting diode can be driven by using the TENG‐UDS with the passive PMC, which cannot be achieved without the PMC. The passive PMC for TENG‐UDS has the advantages of simple structure, low energy consumption, and high energy storage efficiency, which provides a promising method for the power management and practical application of TENG. Abstract : Herein a triboelectric nanogenerator with an unidirectional switch (TENG‐UDS) is demonstrated, which provides maximized output energy regardless of the load resistance. A passive power management circuit with a simple structure and high energy storage efficiency is designed based on this TENG‐UDS, which has a maximum energy storage efficiency of 48%.